Bone marrow-derived epithelial cells and hair follicle stem cells contribute to development of chronic cutaneous neoplasms - Heuijoon Park (Nature Portfolio, 2018)
Bone marrow-derived epithelial cells can be recruited to sites of chronic inflammation. Here, the authors using allogenic bone marrow transplantation in a multistage murine cutaneous carcinogenesis model show that bone marrow-derived epithelial cells and hair follicle stem cells are recruited to cutaneous neoplasms during tumor promotion of carcinogen-exposed skin and bone marrow.